2010
DOI: 10.1007/s00268-010-0889-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Risk Factors for Intra‐ and Postoperative Complications in 526 Laparoscopic Sigmoid Resections due to Recurrent Diverticulitis: A Multivariate Analysis

Abstract: Background Laparoscopic sigmoid resection is a feasible and frequent operation for patients who suffer from recurrent diverticulitis. There is still an ongoing debate about the optimal timing for surgery in patients who suffer from recurrent diverticulitis episodes. In elective situations the complication rate for this procedure is moderate, but there are patients at high risk for perioperative complications. The few identified risk factors so far refer to open surgery. Data for the elective laparoscopic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 24 publications
3
23
1
3
Order By: Relevance
“…Overall, intraoperative adverse events did not change over time even after we corrected for age, gender, BMI, and malignant disease, the most commonly identified factors associated with an intraoperative adverse event [13,[24][25][26]. However, an intraoperative adverse event significantly increased postoperative morbidity from 17 to 33 % in our study.…”
Section: Discussioncontrasting
confidence: 46%
“…Overall, intraoperative adverse events did not change over time even after we corrected for age, gender, BMI, and malignant disease, the most commonly identified factors associated with an intraoperative adverse event [13,[24][25][26]. However, an intraoperative adverse event significantly increased postoperative morbidity from 17 to 33 % in our study.…”
Section: Discussioncontrasting
confidence: 46%
“…For instance, from the patients who underwent laparoscopic sigmoid resection for diverticular disease, 1.14% had cardiac complications [16], while 11.2% patients suffered an AMI after colorectal surgery [17]. Patients undergoing head and neck surgery had an AMI rate of 0.3% [18].…”
Section: Discussionmentioning
confidence: 99%
“…In a large study with 526 patients who underwent laparoscopic sigmoid resection for recurrent diverticulitis, male gender, anemia, previous myocardial infarction, heart failure and level of surgeons’ experience were independent predictive risk factors for postoperative complications such as anastomotic leakage, SSI and bleeding [25]. The same study reported age (≥75 years) as the only independent risk factor for intra-operative complications like bowel and ureteric injury and bleeding; however, these authors did not report on pre-operative abscess or fistula.…”
Section: Discussionmentioning
confidence: 99%